ESTONIA AND SOUTH KOREA-NEIGHBOURS IN THE PISA-STATISTICS - Mare Leino (PUPIL: International Journal of Teaching, Education and Learning, 2025)
In 2022 in the PISA, Estonia had the 4. places in the world, right after Japan, Singapur and South-Korea. (In previous PISA, 4 years ago, Estonia was a bit better). So - we have been neighbours in this top-list many years already, which is interesting, as one country locates in Asia, the other in East-Europe; one used to have kind of collectivists value system, the other is rather individualistic. What kind of aspects put us together in the PISA-list? My guess is that the social aspect shapes the statistics, especially the social benefits: unemployments money, support for child care, pensions, the role of state in case of poorness, etc. The education is almost the only field, where people may influence their quality of life: better education enables to get better job with higher salary. Unemployed without education can not cope, if the support from the state is not good enough.The GDP per capita in Estonia is equivalent to 86% of the world’s average, which is worse, for example than Spain and Portugal. According to the Bank of Estonia, in 2021 the 5% of inhabitants owns 46% of all assets in the country; and 50% of people has only 7% of assets. In Estonia, the social benefits are not good enough. The state is poorer than, for example Nordic countries. In Norway, the GDP per capita is 625 percent of the world’s. But in the PISA list Norway has the place nr 32, which is even under the international average level. In the rich countries people can cope anyway, even if they were not successful in general education.The GDP per capita in South Korea is equivalent to 270 percent of the world’s average. Huntington wrote, that in 1960ies in South-Korea and in Ghana the GDP was almost equal; in both countries, the export of raw materials dominated, and both countries got a significant, almost equal help from outside. But 30 years later the economy of South-Korea reached the 14.th place in the world, which was similar to Greek. Ghana´s story was not so successful – in 1990 the GDP in Ghana was only 1/15 from the GDP of South-Korea. Huntington explained these statistics with the culture. He wrote that people in South-Korea value investment, sustainability, hard work, education, discipline, order, economy and efficiency. The same words can be used for Estonians, too.To be the neighbors in the PISA is not the problem. But: despite the high position in PISA, students both in Estonia and South-Korea are not happy. The aim of this article is to find out the background information: what is the price of high academic achievements. I am going to analyze the PISA statistics through the economy and cultural aspects of countries. The research method is a secondary data analysis, as I´ll focus on the statistics, found from the Internet. The hypothesis is that the study eagerness depends partly on the GDP of the country, and on the cultural background. In context of the culture there are several sub-aspects: values, social capital, individualism/collectivism, level of democracy and human rights, etc.